1979
DOI: 10.1210/endo-105-1-195
|View full text |Cite
|
Sign up to set email alerts
|

Serum Prolactin Concentrations during Hormonally Induced Pseudopregnancy in the Rat

Abstract: Treatment of 5-day cyclic rats with 10 or 100 microgram estradiol benzoate on the day of estrus induced a luteal phase in all animals studied. On the other hand, an injection with 1 microgram estradiol benzoate given on the same day failed to induce pseudopregnancy. When 10 mg progesterone were injected on the day of estrus, about 50% of the rats became pseudopregnant, whereas most of the remaining rats had a 6-day cycle. The injection of 10 or 100 microgram estradiol benzoate or 10 mg progesterone induced a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0
1

Year Published

1984
1984
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 27 publications
2
9
0
1
Order By: Relevance
“…4). This fact is consistent with results in adult rats in which a single injection of progesterone at the same time as ovariectomy performed on the day of oestrus induces nocturnal prolactin surges (de Greef & Zeilmaker, 1979;Murakami et ai, 1980). On the other hand, nocturnal prolactin surges during the pubertal stage could be induced by progesterone administration even at 6 days after the ovariectomy (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…4). This fact is consistent with results in adult rats in which a single injection of progesterone at the same time as ovariectomy performed on the day of oestrus induces nocturnal prolactin surges (de Greef & Zeilmaker, 1979;Murakami et ai, 1980). On the other hand, nocturnal prolactin surges during the pubertal stage could be induced by progesterone administration even at 6 days after the ovariectomy (Fig.…”
Section: Discussionsupporting
confidence: 90%
“…It has been reported by our (Murakami et al, 1980) and other (de Greef and Zeilmaker, 1979) groups that the single injection of progesterone to the estrous rats induces pseudopregnancy with daily PRL surges beginning two days after the injection. In these rats, the plasma level of PRL rose immediately after the injection to nearly the peak of the PRL surge, and the level remained high for1or2days.…”
Section: Discussionsupporting
confidence: 50%
“…Though it is known that the daily PRL surges can be induced by a single treatment with an extremely high dosage of progesterone (de Greef and Zeilmaker, 1979;Murakami et al, 1980), the effectiveness of a continuously maintained high, but not pharmacologically high, plasma progesterone level on the initiation of PRL surges has not been investigated.…”
mentioning
confidence: 99%
“…It has been demonstrated that the effect of estrogen on the diurnal PRL surge is similar to its effect on the proestrous afternoon surge of PRL [40]. Treatment with estrogen or progesterone on the day of estrous induced twice daily PRL surges as seen in mated animals [41]. The present study, for the first time, demonstrated that neuronal activity changed in the mPOA, mAMYG and VMH both during the proestrous PRL surge and following mating, suggesting that both hormonal and vaginocervical stimuli are processed and possibly integrated in these brain regions.…”
Section: Discussionmentioning
confidence: 99%